Integração dos processos de ouvidoria de uma agência reguladora com os agentes regulados: o caso da Agência Nacional de Energia Elétrica - ANEEL - Pinho, Roberto Dantas (2002)
The creation of regulatory agencies in the Energy Industry makes it necessary to establish new ways of relationship among industry players, government and society. This dissertation presents an ombudsman service as it was adopted at The Brazilian Electricity Regulatory Agency - ANEEL, its conceptual model, which is focused on building a solicitation classification tree, and the technological solution adopted on its deployment. The solicitation classification tree has information associated with every kind of solicitation present on its structure. This information makes the classification tree useful not only to generate statistics, but also to increase the efficiency of the ombudsman service and to standardize the answers produced by it. Frequent society demands, among other factors, were used to build an initial solicitation classification tree. The technological solution used to implement the proposed conceptual model is based on a workflow process. It allows the inquiries to be treated by several agents on different locations. The dissertation also identifies the ombudsman processes performed by the main electrical energy agents. It goes on to show how it is possible to adopt the same classification strategy on those agents so that consolidated data - representing all the population - can be obtained by the ombudsman service at ANEEL. Lastly, the dissertation discusses how the collected data can be used to analyze the performance of the regulated agents, prioritize regulatory and inspection actions, identify problems, and support regulation proposals. It goes on to discuss some of the data exploration techniques that can be used to analyze the collected data.